1995
DOI: 10.1038/bjc.1995.127
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for benign ovarian teratomas

Abstract: (Simon et al., 1985;Westhoff et al., 1988). Epidemiological data on the issue, however, are scanty.We report the results of a cas-control study on risk factors for benign ovarian teratomas conducted in the framework of a larger study on risk factors for benign and malignant ovarian diseases (Paramni et al., 1989;1991a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Despite its high prevalence, studies have frequently focused on malignant transformation, because it is the most commonly encountered germ cell neoplasm of the ovaries. Although one previous study showed an increased prevalence of infertility in women with mature cystic teratomas of ovary,15 direct evidence of an association thereof is lacking.…”
Section: Introductionmentioning
confidence: 93%
“…Despite its high prevalence, studies have frequently focused on malignant transformation, because it is the most commonly encountered germ cell neoplasm of the ovaries. Although one previous study showed an increased prevalence of infertility in women with mature cystic teratomas of ovary,15 direct evidence of an association thereof is lacking.…”
Section: Introductionmentioning
confidence: 93%
“…Of the cases, 19 (22%) occurred in nulliparous patients, 3 (3%) occurred in grand multiparous patients, and 30 (34%) cases did not mention parity. 4 Case Reports in Obstetrics and Gynecology 80 cases (91%) were of unilateral dermoid cysts, and 8 cases (9%) were bilateral dermoid cysts. In all these cases, the unruptured contralateral cyst was also removed.…”
Section: Resultsmentioning
confidence: 99%
“…In premenopausal women who present with an ovarian mass, 70% of those are attributed to a dermoid cyst; however, its true incidence is much lower in postmenopausal women at 20% [1]. The incidence is estimated at 10 per 100,000 women per year [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recent epidemiological stud ies, however, suggest that only women with decreased fertility and higher education were at increased risk, but provide no satisfactory explanation for this association [10]. Data on the reproductive history and educational sta tus of patients included in this retrospective study were unavailable.…”
Section: Discussionmentioning
confidence: 96%